Pembinaan Nilai-Nilai Islam Dan Pendapatan Melalui Tanaman Hidroponik di RT 19 RW 03 Kelurahan Bumi Ayu Kecamatan Selebar - Khasanah, Mahrifatun; Nisa, Mona Chairun; Azzahra, Tjik Siti Afifa; Fryanti, Yunida Een (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This research focuses on improving the knowledge, skills and income of the community of RT 19 RW 03 Kelurahan Bumi Ayu through the application of hydroponics based on Islamic values. By actively involving the community and using a participatory approach, the program succeeded in improving the local economy and strengthening the social and spiritual aspects of the community. The results show that hydroponic business development supported by religious and social values can be an effective solution in empowering communities with significant economic benefits and environmental sustainability.